Robótica educacional no ensino de matemática - Cunha, Jaime Mendes da (2024)
With the advancement of technology, education has been opening up space for the insertion of new tools for the teaching-learning process. However, the use of equipment and software requires technical training from the teacher combined with the development of methodologies for applying these tools in teaching the topic covered. Faced with this problem, this work aims to discuss the teaching-learning process of students through the use of robotics in the classroom, to facilitate the learning of mathematics content. In this sense, this research proposes the investigation of successful practices in the use of robotics in the classroom, both in Elementary II and High School. The research used a qualitative bibliographic review, with a time frame of 10 years, in the Scielo and Google Scholar databases. The research also explored how robotics can promote collaborative learning and group problem solving, skills essential for students' academic and professional development. Educational robotics has proven effective in promoting a dynamic and interactive learning environment, where students can experiment, make mistakes and learn in a meaningful way. The research also highlighted challenges such as the need for continued teacher training, the availability of technological resources and the initial resistance of educators and students. This work contributes to knowledge about the use of technology in education and offers practical information for educators who wish to innovate their pedagogical practices. By integrating educational robotics into mathematics teaching, it is possible to transform the perception of the subject, making it more attractive and accessible. The research concludes that, despite the challenges, the adoption of educational robotics can revolutionize mathematics teaching, promoting holistic and adaptive learning, aligned with the demands of the 21st century